2004
DOI: 10.1016/s0741-5214(03)00922-4
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative sum failure analysis of the learning curve with endovascular abdominal aortic aneurysm repair

Abstract: Success rates with endovascular aneurysm repair will improve with an individual's experience. The CUSUM method is a valuable tool in the evaluation of this learning curve, which has credentialing and training implications. Although acceptable results were obtained throughout the study period, this analysis indicates that 60 endovascular aneurysm repairs, or 20 with an individual device, are necessary before optimal rates of initial clinical success can be achieved. These results can be achieved more readily wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 49 publications
0
71
0
7
Order By: Relevance
“…Endovasküler aortik onarım cerrahiye iyi bir alternatif olmakla beraber, öğrenme dönemleri daha yüksek mortalite ve morbititeye sahip işlemlerdir (11,12) . Üçüncü basamak sağlık hizmeti veren kurumumuzda artan oranda uyguladığımız işlemlerin ilk dönem tecrübemiz incelendiğinde hastane içi ölüm oranları-mız tüm grupta %7 iken, acil olgularda %13.3 elektif olgularda ise %5.3 oranlarıyla daha tecrübeli merkezlerin oranlarıyla benzerlik göstermekteydi (3,11,14) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Endovasküler aortik onarım cerrahiye iyi bir alternatif olmakla beraber, öğrenme dönemleri daha yüksek mortalite ve morbititeye sahip işlemlerdir (11,12) . Üçüncü basamak sağlık hizmeti veren kurumumuzda artan oranda uyguladığımız işlemlerin ilk dönem tecrübemiz incelendiğinde hastane içi ölüm oranları-mız tüm grupta %7 iken, acil olgularda %13.3 elektif olgularda ise %5.3 oranlarıyla daha tecrübeli merkezlerin oranlarıyla benzerlik göstermekteydi (3,11,14) .…”
Section: Discussionunclassified
“…Endovasküler uygulamalar öğrenme dönemlerinde daha yüksek mortalite ve morbidite ile ilişkili işlemlerdir (11,12) . Ülkemizden yapılan bildiriler sınırlı hasta sayısını veya geniş dönemi kapsamaktadır.…”
unclassified
“…LOBATO et al (23) have shown that 55 endovascular aneurysm repairs were necessary to achieve optimal results ; and that the interval between the procedures was also important, with one case every 10 days being the minimal workload to achieve these success rates. FORBES et al (24) in their analysis suggested that 60 elective endovascular repairs, or 20 with a specific device, are required to obtain optimal initial clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…The initial use of aorto-aortic tube endograft determined early failure of EVAR for distal aortic attachment site complications and device migrations (24). Nevertheless MAY et al (11) in their experience concluded that there are risks inherent in the endograft method rather than iatrogenic complications that occur as a learning curve phenomenon : new devices have modified the type of the adverse events but not their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although attempts have been made to understand the learning curves associated with various procedures, the neurosurgical and spine literature is lacking any such studies compared with what is found in other surgical fields. 1,2,5,6,8 There are certainly many variables associated with how an individual learns. In an attempt to understand this process we evaluated a single resident/attending team as the resident learned how to perform a minimal-access TLIF.…”
mentioning
confidence: 99%